Overexpression of eIF5 or its protein mimic 5MP perturbs eIF2 function and induces ATF4 translation through delayed re-initiation - Kozel, Caitlin; Thompson, Brytteny; Hustak, Samantha; Moore, Chelsea; Nakashima, A.; Singh, Chingakham Ranjit; Reid, Megan; Cox, Christian; Papadopoulos, E.; Luna, R. E.; Anderson, Abbey; Tagami, H.; et al. (My University, 2017)
ATF4 is a pro-oncogenic transcription factor whose translation is activated by eIF2 phosphorylation through delayed re-initiation involving two uORFs in the mRNA leader. However, in yeast, the effect of eIF2 phosphorylation can be mimicked by eIF5 overexpression, which turns eIF5 into translational inhibitor, thereby promoting translation of GCN4, the yeast ATF4 equivalent. Furthermore, regulatory protein termed eIF5-mimic protein (5MP) can bind eIF2 and inhibit general translation. Here, we show that 5MP1 overexpression in human cells leads to strong formation of 5MP1:eIF2 complex, nearly comparable to that of eIF5:eIF2 complex produced by eIF5 overexpression. Overexpression of eIF5, 5MP1 and 5MP2, the second human paralog, promotes ATF4 expression in certain types of human cells including fibrosarcoma. 5MP overexpression also induces ATF4 expression in Drosophila. The knockdown of 5MP1 in fibrosarcoma attenuates ATF4 expression and its tumor formation on nude mice. Since 5MP2 is overproduced in salivary mucoepidermoid carcinoma, we propose that overexpression of eIF5 and 5MP induces translation of ATF4 and potentially other genes with uORFs in their mRNA leaders through delayed re-initiation, thereby enhancing the survival of normal and cancer cells under stress conditions.
Citation: Kozel, C., Thompson, B., Hustak, S., Moore, C., Nakashima, A., Singh, C. R., . . . Asano, K. (2016). Overexpression of eIF5 or its protein mimic 5MP perturbs eIF2 function and induces ATF4 translation through delayed re-initiation. Nucleic Acids Research, 44(18), 8704-8713. doi:10.1093/nar/gkw559
Keywords: Guanine-Nucleotide Exchange; Start Codon Recognition; Multifactor; Complex; Eif5-Mimic Protein; Mammalian-Cells